1995
DOI: 10.1007/bf00401841
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus and impaired glucose tolerance in parents of women with gestational diabetes

Abstract: Summary Nuclear families of non-insulin-dependent diabetic (NIDDM) patients are uncommon, as usually one or both parents have died. In order to aid identification of complete nuclear families, we have ascertained the disease process at a younger age by studying subjects with previous gestational diabetes. One hundred women who had had gestational diabetes, age (+ SD) 38 (6) years, were screened by fasting plasma glucose (fpg). Sixty-one were found to have either fasting hyperglycaemia (5.5 _< fpg < 7.8 mmol/1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…Other reports examining hGDM have also found that both maternal-only and paternal-only diabetes histories confer greater hGDM risk 3-6. In these other reports, the degree of excess risk with maternal-only history compared to paternal-only history ranges from little to none,4, 6 as in our report, to mildly increased,5 to double 3.…”
Section: Commentsupporting
confidence: 74%
See 1 more Smart Citation
“…Other reports examining hGDM have also found that both maternal-only and paternal-only diabetes histories confer greater hGDM risk 3-6. In these other reports, the degree of excess risk with maternal-only history compared to paternal-only history ranges from little to none,4, 6 as in our report, to mildly increased,5 to double 3.…”
Section: Commentsupporting
confidence: 74%
“…In these other reports, the degree of excess risk with maternal-only history compared to paternal-only history ranges from little to none,4, 6 as in our report, to mildly increased,5 to double 3. Excess risk with a maternal-only history would imply intrauterine, mitochondrial, or other epigenetic influences.…”
Section: Commentsupporting
confidence: 56%
“…Other problems arise from various diagnostic criteria of the condition, which have been changed over time, and heterogeneous guidelines for GDM screening in different countries. Additional difficulties are related to environmental influences and racial differences [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Familial clustering of GDM and T2D have been studied, linking T2D and impaired glucose tolerance in families with GDM [15] and there is evidence of a higher incidence of T2D in mothers of women with GDM [16]. …”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%